Enhancing sustainable practice in social housing delivery: A focus on South Africa, Soweto’s urban development - Makalima, Mzuchumile (Acta Carolus Robertus, 2023)
This paper explores sustainable practices in social housing delivery in Soweto, South Africa, and their influence on urban development. The research aims to assess the current state of sustainable practices and identify challenges and opportunities for enhancing sustainability. Through interviews with government officials, community leaders, young residents, and construction experts, this paper shows existing sustainable initiatives, such as solar panels and recycling, driven by government policies. However, challenges, including budget constraints and the need for community education, persist. Recommendations emphasize collaboration, clear communication, community engagement, and local resource utilization. This study contributes to the ongoing discourse on sustainable urban development, offering insights that can guide Soweto toward a greener and more inclusive future.